2018
DOI: 10.2147/ceor.s171560
|View full text |Cite
|
Sign up to set email alerts
|

Budget impact model of secukinumab for the treatment of moderate-to-severe psoriasis, psoriatic arthritis, and ankylosing spondylitis in Italy: a cross-indication initiative

Abstract: ObjectiveSecukinumab, a fully human monoclonal IgG1 antibody that selectively neutralizes the proinflammatory cytokine IL-17A, has been approved in Europe in 2015 for the treatment of adult patients with moderate-to-severe plaque psoriasis, psoriatic arthritis (PsA), and ankylosing spondylitis (AS). This analysis assessed the budget impact of introduction of secukinumab to the Italian market for all three indications from the perspective of the Italian National Health Service.Materials and methodsA cross-indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 71 publications
0
10
1
Order By: Relevance
“…Clinical studies have labelled secukinumab, which is a humanized, monoclonal antibody anti-IL-17A, suitable as therapy for moderate to severe psoriasis, hypertrophic palmoplantaris psoriasis, and generalized pustular psoriasis in adult patients, in cases of prior failure to systemic therapies, contraindications, or intolerability to systemic agents. Also psoriatic arthritis and ankylosing spondylitis not responding to systemic agents or moderate-to-severe disease in adult patients are indications for secukinumab [15,16,[24][25][26]. Its clinical efficacy in psoriasis and safety have been well demonstrated in many clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have labelled secukinumab, which is a humanized, monoclonal antibody anti-IL-17A, suitable as therapy for moderate to severe psoriasis, hypertrophic palmoplantaris psoriasis, and generalized pustular psoriasis in adult patients, in cases of prior failure to systemic therapies, contraindications, or intolerability to systemic agents. Also psoriatic arthritis and ankylosing spondylitis not responding to systemic agents or moderate-to-severe disease in adult patients are indications for secukinumab [15,16,[24][25][26]. Its clinical efficacy in psoriasis and safety have been well demonstrated in many clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic, immune-mediated, inflammatory diseases such as psoriasis, psoriatic arthritis and AS are associated with substantial healthcare costs [ 49 ]. In the NICE guidance, secukinumab was reported to be a cost-effective use of health system resources for AS, regardless of previous TNF inhibitor use [ 44 ].…”
Section: Place Of Secukinumab In the Management Of Ankylosing Spondylmentioning
confidence: 99%
“…Indeed, a modelled pharmacoeconomic study from a UK National Health Service perspective suggests that secukinumab is a cost-effective treatment option for biologic-naive and -experienced patients with active AS [ 50 ]. Model-based budget impact analyses in Italy [ 49 ], Finland [ 51 ], Greece [ 52 ] and Brazil [ 53 ] also demonstrated that secukinumab is a cost-saving option for the treatment of AS. In cost-effectiveness analyses in Portugal [ 54 ], Tunisia [ 55 ] and Korea [ 56 ], the costs per responder were lower with secukinumab than with adalimumab in patients with AS.…”
Section: Place Of Secukinumab In the Management Of Ankylosing Spondylmentioning
confidence: 99%
“…Among study biologic drugs, secukinumab was the most frequently used, followed by ustekinumab, TNF‐inhibitors, and ixekizumab, a ranking that roughly corresponds to the prescription trends for moderate–severe plaque psoriasis in Italy 35 . In any case, the range of currently available biological treatments for moderate–severe plaque psoriasis was represented.…”
Section: Discussionmentioning
confidence: 99%
“…a trends for moderate-severe plaque psoriasis in Italy. 35 In any case, the range of currently available biological treatments for moderatesevere plaque psoriasis was represented. Topical treatments and conventional systemic medications for psoriasis were ongoing in 35% and 8% of patients, respectively.…”
Section: Discussionmentioning
confidence: 99%